(untitled) (The International Journal of Educational Sciences and Arts, 2026)
The present study aimed to develop a Parental Support Scale for university students and examine its psychometric properties in light of the theoretical frameworks and previous literature. The study adopted a descriptive-analytical approach, and the scale was developed based on Self-Determination Theory and Social Support Theory, in a manner consistent with the developmental characteristics of emerging adulthood represented by the university stage. The preliminary version of the scale consisted of 32 items, which underwent expert review and revision, resulting in an initial version of 24 items distributed across four dimensions: emotional support, practical and financial support, informational support and guidance, and respect and autonomy support. The scale was administered to a sample of 452 undergraduate students from universities in Jeddah. The results of the Confirmatory Factor Analysis (CFA) indicated high levels of construct validity, convergent validity, and discriminant validity, in addition to high reliability and internal consistency indicators. The model also demonstrated acceptable goodness-of-fit indices, supporting the suitability of the scale for use with university students. The study recommended using the scale in the Arab university context and conducting further research on parental support among university students.